The Infiltration of Mathematical Modeling Thoughts in College Mathematics Teaching. Issue 5 (February 2019) - Xianfang, Tang; Yachao, Jia; Ru, Zhang
Abstract: Integrating mathematical modeling into the process of higher mathematics teaching in universities is crucial to the cultivation of students' practical and innovative abilities. It is the mainstream direction of reforming mathematics teaching in universities under the new situation, and will play a decisive role in the teaching effect of mathematics in higher education institutions. This paper begins with the basic meaning of mathematical modeling thoughts, analyzes the importance of introducing mathematical modeling ideas in college mathematics teaching, and finally puts forward the specific countermeasures to infiltrate mathematical modeling ideas into university mathematics teaching. It provides useful reference for improving the mathematics teaching effect in colleges and universities.